Göbekli Tepe, Türkei: Die Arbeiten des Jahres 2014 - Schmidt, Klaus; Clare, Lee; Dietrich, Oliver; Köksal-Schmidt, Çiğdem; Notroff, Jens (e-Forschungsberichte des DAI, 2023)
The tell of Göbekli Tepe is situated a few kilometres to the northeast of Şanlıurfa in south-eastern Turkey. The immense ruin hill formed by the debris of monumental constructions dating back to the 10th and 9th millennium BC (the Pre-Pottery Neolithic) has been excavated systematically since 1995. Recent excavation campaigns focussed on preliminary work for the erection of permanent shelter structures to preserve the site.